Exploring metallicity-dependent rates of Type Ia supernovae and their impact on galaxy formation. Issue 2 (10th August 2022) - Gandhi, Pratik J; Wetzel, Andrew; Hopkins, Philip F; Shappee, Benjamin J; Wheeler, Coral; Faucher-Giguère, Claude-André
ABSTRACT: Type Ia supernovae are critical for feedback and elemental enrichment in galaxies. Recent surveys like the All-Sky Automated Survey for Supernova (ASAS-SN) and the Dark Energy Survey (DES) find that the specific supernova Ia rate at z ∼ 0 may be ≲20–50× higher in lower mass galaxies than at Milky Way-mass. Independently, observations show that the close-binary fraction of solar-type Milky Way stars is higher at lower metallicity. Motivated by these observations, we use the FIRE-2 cosmological zoom-in simulations to explore the impact of metallicity-dependent rate models on galaxies of $M_* \sim 10^7\!-\!10^{11}\, \rm {M}_{\odot }$ . First, we benchmark our simulated star formation histories against observations, and show that the assumed stellar mass functions play a major role in determining the degree of tension between observations and metallicity-independent rate models, potentially causing ASAS-SN and DES observations to agree more than might appear. Models in which the supernova Ia rate increases with decreasing metallicity ($\propto Z^{-0.5 \, \, \rm {to} \, \, -1}$ ) provide significantly better agreement with observations. Encouragingly, these rate increases (≳10× in low-mass galaxies) do not significantly impact galaxy masses and morphologies, which remain largely unaffected except for our most extreme models. We explore implications for both [Fe/H] and [$\alpha /\rm {Fe}$ ] enrichment; metallicity-dependent rate models can improve agreement with the observed stellar mass–metallicity relations in low-mass galaxies. Our results demonstrate that a range of metallicity-dependent rate models are viable for galaxy formation and motivate future work.